Kaji eksperimental penyimpanan biogas dengan adsorben karbon aktif komersial - Antara Putra, Dewa Made; Sucipta, Made; Wijaksana, Hendra (Teknik Desain Mekanika, 2023)
Abstract Biogas as an alternative energy can be used as fuel. Currently, the society uses biogas produced by Simantri using plastic bags but has low storage efficiency. One way to increase biogas storage is to use ANG (Adsorbed Natural Gas) technology filled with activated carbon as an adsorbent. The main objective of this study was to determine the storage capacity of biogas filled with commercial activated carbon made from bamboo on the market. The activated carbon used is ground and sieved with a mesh size of 70-230. The biogas storage test was carried out until the tube pressure reached 100 psi and the mass of activated carbon was 15 grams. As a comparison, the test was also carried out on empty tubes without activated carbon. In an empty cylinder, the mass of biogas stored at a pressure of 100 psi is only 30.8 grams, while in a tube filled with activated carbon, the same pressure can store 32.1 grams. Keyword: Biogas storage, activated carbon, ANG